Between memory and modernity: The poetic geography of martin Camaj - Isufaj, Viola; Bora, Armand (International Journal of Innovative Research and Scientific Studies, 2025)
This study explores the poetic universe of Martin Camaj, a seminal figure in Albanian literature, positioned at the intersection of Albanian cultural memory and European modernist aesthetics. Anchored in the mythic and natural topography of Albania, Camaj’s poetry evolves through a cosmopolitan lens shaped by exile, displacement, and intellectual engagement with European literary movements. His early verse reconstructs Albanian identity through symbolic landscapes and ancestral memory, while his later work adopts a hermetic style that reflects the existential and aesthetic dimensions of exile. Thus, his poetry emerges as a layered palimpsest, wherein archaic myth, symbolic geography, and linguistic experimentation coalesce to articulate a poetics of restoration. Camaj’s engagement with themes of loss, solitude, and regeneration is interpreted within broader frameworks of cultural displacement, modern identity, and literary resistance. The paper further argues that Camaj’s transnational position and stylistic hybridity challenge traditional conceptions of Albanian literature, offering a model for understanding the exilic condition not as marginalization but as a site of creative renewal. Drawing on close readings of key poems, this study argues that Camaj’s poetics enact a restoration of cultural continuity, transforming absence into an aesthetic and ontological paradigm. His work stands as a testament to the power of poetry to preserve, reimagine, and unify identity across fractured geographies.